Analisis Tegangan Output Dan Tegangan Diode Penyearah Jembatan Gelombang Penuh 1 Phase Menggunakan MATLAB SIMULINK - Irvan Dinata; Meisan Jaya Haro; Meliana Rointan Silaban (Kampus Akademik Publiser, 2026)
A rectifier is a power electronics circuit that functions to convert alternating current (AC) voltage into direct current (DC) voltage required by various electronic devices. This study aims to analyze the characteristics of the output voltage and the voltage across the diodes in a single-phase full-wave bridge rectifier circuit using MATLAB Simulink software. The research method used is a simulation method by designing a circuit model consisting of an AC voltage source, four diodes arranged as a bridge rectifier, a load, and a filter capacitor. The simulation results show that the input voltage has a sinusoidal waveform with a peak value of approximately 120 V. After the rectification process, the output voltage becomes a pulsating DC voltage with a peak value of about 93 V, which is influenced by the voltage drop across the diodes. The addition of a filter capacitor is able to reduce the voltage ripple, resulting in a more stable load voltage in the range of 84 V to 87 V. The results of this study indicate that the full-wave bridge rectifier circuit is capable of converting AC voltage into DC voltage effectively, and MATLAB Simulink simulation can be used as an effective analysis tool for studying the characteristics of power electronics circuits before implementation in real systems.